Segmented Housing Search - Piazzesi, Monika; Schneider, Martin; Stroebel, Johannes (American Economic Review, 2020)
We study housing markets with multiple segments searched by heterogeneous clienteles. In the San Francisco Bay Area, search activity and inventory covary negatively across cities, but positively across market segments within cities. A quantitative search model shows how the endogenous flow of broad searchers to high-inventory segments within their search ranges induces a positive relationship between inventory and search activity across segments with a large common clientele. The prevalence of broad searchers shapes the response of housing markets to localized supply and demand shocks. Broad searchers help spread shocks across many segments and reduce their effect on local market activity. (JEL D83, R21, R31)